In silico trials using Monte Carlo simulation to evaluate ciprofloxacin and levofloxacin dosing in critically ill patients receiving prolonged intermittent renal replacement therapy. Issue 1 (December 2016) - Lewis, Susan; Chaijamorn, Weerachai; Shaw, Alexander; Mueller, Bruce
Abstract Background Prolonged intermittent renal replacement therapy (PIRRT) is a growing option to treat acute kidney injury in critically ill patients, but absent pharmacokinetic data challenge optimal drug dosing. Inappropriate antibiotic dosing can cause widespread bacterial resistance and decreased antibiotic utility. The purpose of this study was to evaluate probability of target attainment (PTA) of various ciprofloxacin and levofloxacin regimens in critically ill patients receiving PIRRT, utilizing Monte Carlo simulation (MCS). Methods The models incorporated published body weights and pharmacokinetic parameters (volume of distribution, non-renal clearance, and extraction coefficients) and their associated variability and ranges. Four different PIRRT effluent/duration combinations (4 L/h × 10 h or 5 L/h × 8 h in hemodialysis or hemofiltration, respectively) occurring at the beginning or 14-16 h after drug administration were modeled. MCS predicted drug disposition during the first 72 h in 5000 virtual patients for each dosing regimen. Desired pharmacodynamic targets to calculate PTA were the 24-h area under the curve/minimum inhibitory concentration (AUC24h :MIC) of ≥125 and ≥50 for Gram-negative and Gram-positive infections, respectively. The "successful" doses were the ones with PTA of 90 % in all PIRRT settings. Results No conventional, FDA-approved regimens attained 90 % of PTA for Gram-negative infection withPseudomonas aeruginosa at the MIC of 1 and 2 mg/L for ciprofloxacin and levofloxacin, respectively. The successful doses (ciprofloxacin 1200 mg loading dose, 800 mg q12h, and levofloxacin 2000 mg loading dose, 1000 mg q24h post-PIRRT) greatly exceed the maximum FDA-approved doses. For Gram-positive infections, a levofloxacin 750 mg loading dose and 500 mg q24h post-PIRRT successfully attained PTA 90 % at the MIC of 1 mg/L forStreptococcus pneumoniae . Conclusions Ciprofloxacin and levofloxacin cannot be recommended as empiric monotherapy for serious Gram-negative infections in patients receiving PIRRT due to suboptimal efficacy. This MCS prediction supports rational dosing decisions to treat infected patients receiving PIRRT and should be used until clinical pharmacokinetic trials are conducted in this population.